Clinical Use of FSH in Male Infertility - Behre, Hermann M. (Frontiers in Endocrinology, 2019)
The established clinical indication for FSH use in male infertility is the treatment of patients with hypogonadotropic hypogonadism for stimulation of spermatogenesis that allows the induction of a clinical pregnancy in the female partner and finally the birth of a healthy child. Several clinical studies with urinary, purified and recombinant FSH preparations in combination with hCG have demonstrated the high treatment efficacy regarding these clinical endpoints. Shortcomings of this hormone therapy are the long duration of treatment, sometimes longer than two years, and the inconvenience of injections every second or third day. However, improvements of therapy might be expected with new hormonal treatment options already available for infertility treatment in the female. FSH use for treatment of patients with normogonadotropic idiopathic infertility and oligozoospermia is still considered experimental in most countries. Recent meta-analyses have shown that FSH can significantly increase pregnancy rates in the female partners of these patients, but the effect-size is relatively low. Therefore, predictive factors for treatment success have to be identified, including FSH pharmacogenetics, to select the right normogonadotropic patients with idiopathic infertility for FSH therapy.